Participation in Sports Betting and Youth Welfare Nexus: An Endogenous Switching Regression Model in Kenyan Perspective - Gathuru, James Muigai (Society & Sustainability, 2022)
This paper seeks to establish the nexus between sports betting participation and youth welfare in Kenya. The focus of the study is the youth based in the Kajiado North constituency which has the highest youth population within the Nairobi metropolitan statistical area. There are 9 universities around the region. The study sample size is 341. Endogenous switching regression estimation is adopted to determine the association between sports betting participation and youth welfare. From the regression analysis, this study obtains a significant and negative coefficient of -1.4971 relating to sports betting and youth welfare. This suggests that sports betting negatively affects youths' overall welfare in a 1.49 percent greater manner than those who abstain from it. It is important to address the factors that lead the youth to participate in sports betting, particularly control of commercials by making it mandatory that they issue disclaimers that doing so may worsen one's welfare. It is also essential to properly educate young people on financial management in order that they may channel their money toward worthwhile endeavors rather than sports betting.